Efektifitas Latihan Aerobik pada Keseimbangan Jalan Penderita Parkinson’s Disease: Meta-Analisis - Fadli, Arif; Noerdjanah, Noerdjanah (Politeknik Kesehatan Kemenkes Surakarta, 2025)
Background: Parkinson's disease (PD) has caused progressive gait impairment with a high risk of falls in daily activities. Aerobic exercise is effective in improving physical fitness with an impact on cognitive function of gait execution. The benefits of aerobic exercise have not been optimally utilized by PD sufferers. Objectives: This systematic review study aims to know effect of aerobic training exercises on gait balance in PD patients. This study will synthesize article data from randomized control trial (RCT) studies in 5 electronic databases PubMed, Google-Scholar, PEDro, OVID, and ScienceDirect. Article searches using search keywords: